Visual working memory performance in aphantasia. (August 2018) - Jacobs, Christianne; Schwarzkopf, Dietrich S.; Silvanto, Juha
Abstract: Aphantasia, i.e., the congenital inability to experience voluntary mental imagery, offers a new model for studying the functional role of mental imagery in (visual) cognition. However, until now, there have been no studies investigating whether aphantasia can be linked to specific impairments in cognitive functioning. Here, we assess visual working memory performance in an aphantasic individual. We find that she performs significantly worse than controls on the most difficult (i.e., requiring the highest degree of precision) visual working memory trials. Surprisingly, her performance on a task designed to involve mental imagery did not differ from controls', although she lacked metacognitive insight into her performance. Together, these results indicate that although a lack of mental imagery can be compensated for under some conditions, mental imagery has a functional role in other areas of visual cognition, one of which is high-precision working memory.